(3GdJShjb GdOhdj (B/s - (3Lj, CHj SYjO GdOjhgs; (3GdYLGQeI, JjSjQ eMeO s ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2000)
(3eaghe GdJShjb GdOhdj hCgejJg(B- (3GdXQha hGdeJZjQGJ GdEbJUGOjI(B- (3GdeDKQGJ GdELJeGYjI hGdKbGajI (B((3GdJeOf(B)- (3GdYhGed hGdeJZjQGJ GdSjGSjI hGdbGfhfjI(B- (3GdaQU GdJShjbjI GdOhdjI(B- (3CTcGd GdONhd Gdi GdCShGb GdNGQLjI(B- (3GdJQhjL hGdEYdGf GdOhdj(B- (3GdJSYjQ Ydi fWGb Ohdj(B- (3GdJhRjY hGdJhRjY GdeGOj OhdjG(B- (3GSJQGJjLjI GdefJLGJ Ydi fWGb Ohdj(B- (3GdJShjb GdOhdj aj GdOhd GdfGejI(B- (3GdJcJdGJ GdEbJUGOjI aj GdCShGb GdYGdejI(B- (3GdEYJHGQGJ GdCNdGbjI hGdELJeGYjI aj GdJShjb GdOhdjs
Keywords: (3GdJLGQI GdNGQLjIs; (3GdJShjbs; (3GdJShjb GdOhdjs